2005
DOI: 10.1029/2005jf000301
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vegetation on flow routing and sedimentation patterns: Three‐dimensional modeling for a tidal marsh

Abstract: [1] A three-dimensional hydrodynamic and sediment transport model was used to study the relative impact of (1) vegetation, (2) micro-topography, and (3) water level fluctuations on the spatial flow and sedimentation patterns in a tidal marsh landscape during single inundation events. The model incorporates three-dimensional (3-D) effects of vegetation on the flow (drag and turbulence). After extensive calibration and validation against field data, the model showed that the 3-D vegetation structure is determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
315
4
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 307 publications
(334 citation statements)
references
References 41 publications
14
315
4
1
Order By: Relevance
“…Within patches of pioneer plants (e.g., Spartina anglica tussocks), tidal currents are reduced and sediment accumulates, raising the plant in the tidal range and resulting in a positive feedback on plant growth. At the same time, the tidal currents accelerate and sediment erodes around the vegetation patches, leading to a negative feedback on plant growth between patches ( Figure 3B) [145,148,165,[177][178][179]. Both feedbacks are density-dependent and exhibit threshold behaviors, i.e., feedbacks only appear to start to influence system dynamics once a threshold plant shoot density is exceeded, and the intensity of the feedbacks increases with increasing shoot density [166].…”
Section: Salt Marshesmentioning
confidence: 99%
“…Within patches of pioneer plants (e.g., Spartina anglica tussocks), tidal currents are reduced and sediment accumulates, raising the plant in the tidal range and resulting in a positive feedback on plant growth. At the same time, the tidal currents accelerate and sediment erodes around the vegetation patches, leading to a negative feedback on plant growth between patches ( Figure 3B) [145,148,165,[177][178][179]. Both feedbacks are density-dependent and exhibit threshold behaviors, i.e., feedbacks only appear to start to influence system dynamics once a threshold plant shoot density is exceeded, and the intensity of the feedbacks increases with increasing shoot density [166].…”
Section: Salt Marshesmentioning
confidence: 99%
“…Intertidal marsh surface water hydrology is characterized by tidal flood and ebb in the channel network [Fagherazzi et al, 1999;Marani et al, 2002Marani et al, , 2003. During especially high tides, the channels fill beyond bankfull capacity and tidal waters flood across the marsh plain, influenced by vegetation roughness [Temmerman et al, 2005;van Proosdij et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that sediment deposition in wetlands is controlled by various factors including the flooding frequency, depth, and duration (French and Spencer 1993;Middelkoop and van der Perk 1998;Reed et al 1999;Temmerman et al 2003;Thonon et al 2007;Schuerch et al 2013), the surface area of the wetland, the suspended sediment load (French and Spencer 1993;Asselman and Middelkoop 1998;Morse et al 2004;Noe et al 2016), and the ability of sediment to settle, which in turn, depends on sediment flow paths (French and Spencer 1993;Siobhan Fennessy et al 1994;Reed et al 1999;Davidson-Arnott et al 2002;Temmerman et al 2003;Anderson and Mitsch 2007;Mitsch et al 2014), wind (Orson et al 1990;Delgado et al 2013), and vegetation (Darke and Megonigal 2003;Temmerman et al 2005;Schile et al 2014;Mitsch et al 2014). These studies were mainly conducted in salt marshes or river flood plains; only few field-based studies were undertaken in freshwater tidal wetlands that represent the transition between these environments.…”
Section: Introductionmentioning
confidence: 99%